Mahmud al-Bulgari. Nahj al-Faradis (Ch. III, sect. 1). - Gibadullin I.R.; Sayfetdinova E.G. (Золотоордынское обозрение)
Purpose: To present the results of the Russian translation of the earliest Istanbul manuscript of the Golden Horde era. Research materials: An excerpt from the work of Mahmud al-Bulgari “Nahj al-Faradis” (“Path to Heaven”). The article contains an excerpt of the first section of the third chapter of “Nahj al-Faradis” by Mahmud al-Bulgari. Results and novelty of the research: “Nahj al-Faradis” by Mahmud al-Bulgari played a significant role in the cultural life of the Tatar people. It is especially interesting in terms of studying the history of social thought in the medieval Volga region as its author relied on a large number of works of famous Muslim theologians. The text is a compilation of religious and ethical teachings with an artistic form given to its embodiment. Fascinating tales and wise parables were crafted to nurture loyalty to Islam and a strong immunity to the temptations that lie in wait for a Muslim on the way to Paradise. The text is replete with fragments from the main works telling about the life of the prophet Muhammad and the interpretation of the hadiths in the works of Muslim jurists, the content of which was transmitted in simple, understandable language.